Natural resources volatility and economic growth: Evidence from the resource-rich region - Arshad Hayat; Muhammad Tahir (Journal of Risk and Financial Management, 2021)
This research paper investigates the impact of natural resources volatility on economic growth. The paper focused on three resource-rich economies, namely, UAE, Saudi Arabia, and Oman. Using data from 1970 to 2016 and employing the autoregressive distributed lag (ARDL) cointegration approach, we found that both natural resources and their volatility matter from the perspective of growth. The study found strong evidence in favor of a positive and statistically significant relationship between natural resources and economic growth for the economies of UAE and Saudi Arabia. Similarly, for the economy of Oman, a positive but insignificant relationship is observed between natural resources and economic growth. However, we found that the volatility of natural resources has a statistically significant negative impact on the economic growth of all three economies. This study contradicts the traditional concept of the resources curse and provides evidence of the resources curse in the form of a negative impact of volatility on economic growth.
Keywords: 330; economic growth; ARDL modeling; GCC; natural resources; volatility